Development of a Model for Quantifying Erodibility of Soils in Eastern Nigeria - Uchenna, Igwe Peter; Chike, Ajadike Joseph; Okonkwo, Ogbu Simeon (Journal of Sustainability and Environmental Management, 2024)
Erodibility is the most variable factor influencing water-induced gully erosion in soil, as it governs the soil’s susceptibility to detachment by opposing the driving force of rainfall erosivity in the gully erosion process. Previous studies on erodibility in Eastern Nigeria have been conducted segmented, lacking a unified model for its quantification. Therefore, this study investigated erodibility and developed a model to quantify it in the region. The nine areas most at risk for gully erosion, one in each of the region’s nine constituent states, were purposively sampled, with one gully from each area then selected through convenient sampling. Data collection instruments included observation, satellite imagery, and experimentation. A total of 81 soil samples—9 from each gully—were collected at depths of 0–30 cm, 30–60 cm, and 60–90 cm to determine the percentages of sand, silt, and clay used to quantify erodibility via Bouyoucos’ Model. Multiple Linear Regression was employed for data analysis. Results indicated that the independent variables (%sand, %silt, and %clay) made significant contributions to the dependent variable (clay ratio/erodibility) across the gullies. Ten models were developed, one for each gully and one general model for the region, as the independent variables made a significant combined contribution (R = .47, R² = .22, p = 0.00 < 0.05 significance level) to the dependent variable. The regression equation produced a model for quantifying erodibility in Eastern Nigeria as follows: erodibility (clay ratio) = 129.04 – 179 sand – 2.237 silt – 9.189 clay. The study recommends: (i) prioritizing the quantification of erodibility in all gully erosion studies to enable the application of appropriate gully remediation strategies, and (ii) the use of the developed erodibility model by built environment professionals in approving development initiatives, among other applications.